[Morphological study of the effect of the drug "Diclocor" in the course of collagen-induced arthritis in rats] - Popov O.S.; Zupanets I.A.; Shebeko S.K. (Морфологія, 2015)
Background. Since NSAIDS have some detrimental side effects, studying new combinations of NDAIDS with other substances could provide a reduction of the dosage of the NSAID while retaining therapeutic effectiveness. Objective. To study the effect of Diclocor on the cartilage morphology in the course of collagen-induced arthritis in rats in comparison with sodium diclofenac and quercetin. Methods. Autoimmune arthritis was reproduced by subcutaneous injections of type II collagen ("Sigma-Aldrich", USA). Morphological studies were performed using standard light microscopy techniques. Results. After treatment with both Diclocor and diclofenac sodium no cartilage destruction was oberved and tissue hyperplasia was low. Some residual effects were observed in the synovial membranes in the Diclocor group, and in periarticular tissues – in the diclofenac sodium group. Under the action of quercetin, there was a sufficiently high level of hyperplastic processes and pannus formation in sinovium. Conclusion. Diclocor and diclofenac sodium express a profound normalizing effect, while Quercetin is less active. Citation: Popov OS, Zupanets IA, Shebeko SK. [Morphological study of the effect of the drug "Diclocor" in the course of collagen-induced arthritis in rats]. Morphologia. 2015;9(3):58-66. Ukrainian.